Development of Islamic Value-based Picture in Biology Learning with the ISI-ARE Model - Pahrudin, Agus; Syafril, Syafrimen; Zahro, Ro'inatuz; Handoko, Akbar; Yaumas, Nova Erlina; Iksan, Zanaton H (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The development of Islamic-based learning models and pictures media recently has become the focus of research in Indonesia, especially the integration between the values of science and religion. This study aimed to develop pictures of media based on Islamic values in Biology learning for high school students. The research and development procedures proposed by Borg & Gall and ADDIE model proposed by Kurt which had been modified into the ISI-ARE (Investigate, Strategy, Improve, Assessment, Realization, and Estimation) model was used as the research method. The data was collected through investigations and questionnaire validation by four experts (material, media, language, and religion). The investigation questionnaire and a media feasibility response questionnaire were distributed to two experienced biology teachers and 20 tenth-grade students (10 males and 10 females). The results showed that the media, religion, and language experts stated that the developed Islamic-based pictures media was highly feasible to be used with the obtained percentage of 90.30 %, 83.70 %, and 81.50 %. However, the material experts rated the media as feasible (75.00 %) and the teachers and students respectively rated the media as highly feasible with a percentage of 75.40 % and 87.20 %. This study illustrates that the Islamic values-based pictures media can be used as an alternative in biology learning.